Knowledge attitude and practice regarding breast feeding mothers of Bundelkhand region of Uttar Pradesh - Barman, Santosh Kumar; Barman, Seema; Patel, Ashok Kumar; Kumar, Navin (International Journal Of Community Medicine And Public Health, 2021)
Background: Breastfeeding is a basic human activity, vital to infant and maternal health and it has massive economic value to households and societies. It has been proved that early initiation of breastfeeding lowers the risk of postpartum hemorrhage and anemia to the mothers, boosts their immunity and reduces the incidence of certain diseases like diabetes and cancer. In this study we assess the socio-demographic characteristics, knowledge, attitude and practice of the mothers regarding breast feeding. Methods: This was a cross-sectional study. It was conducted for a period of nine month from July 2019 to March 2020 at Government Allopathic Medical College, Banda. Total 160 children in the age group of 0-6 months came at immunization clinic of pediatric OPD. Results: Total numbers of children studied during the study period were 160 out of which 54.37% were male and 46.62% were females. Maximum number of mothers (38.75%) belong to the age group of 25-30 years followed by 21-25 years (26.87%). 38.12% of the mothers start breastfeeding within one hour, 46.87% between 1-6 hour and 60% of the mothers breastfed their babies on demand. Conclusions: The participants had good knowledge and attitude regarding breastfeeding but there was a noticeable deficit in the use of this knowledge in the breastfeeding practices which points towards the gap in the education and counselling of women regarding breast feeding.